Preparation of organic-solvent free liposome of Piper albi Linn extract in solution and powder form - Eri Amalia; Iyan Sopyan; Norisca Aliza Putriana; Sriwidodo Sriwidodo; Anas Subarnas (Indonesian Journal of Pharmaceutics, 2021)
Piperine is bioactive alkaloid extracted from white pepper (Piper albi Linn) with several beneficial pharmacological activities. It is also known to enhance the bioavailability of several limited solubilities of other compounds such as curcumin and resveratrol. Nevertheless, due to its poorly water-soluble character, piperine and extract of white pepper are less applied among other plant extracts. Therefore, our research focussed on the engineering of white pepper extract standardized to piperine in liposome solution and liposome powder for further preparation of various pharmaceutical dosage forms.Our research in preparation of extracted white pepper in liposome delivery system successfully prepared spheric liposome solution with 98.92%±1.17% and an average size of 398.7 nm. The liposome was also successfully prepared in dry powder form with sucrose as a carrier for liposome protection. The rehydration is successfully forming a spheric shape with a similar profile to the initial liposome solution. This research paves the way for scalable white pepper extract liposome preparation without the utilization of toxic organic solvent, to produce the commercial solvent-free product in the future.Keywords: Piperine, Piper albi Linn, liposome, extract, organic solvent-free, drug delivery system, spray dry